PENGARUH MOTIVASI BELAJAR DAN KREATIVITAS BELAJAR TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI MADRASAH ALIYAH NEGERI SE-KOTA PEKANBARU - Dewi Susanti; Razali Pebrianto (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
This study aims to see whether there is an influence of learning motivation and learning creativity on student achievement in Islamic Religious Education subjects in State Madrasah Aliyah in Pekanbaru City. The research method uses quantitative research types using correlational analysis techniques. The population in this study were all State Madrasah Aliyah students in Pekanbaru City totaling 2,042 people. The sample in this study was taken by proportionate random sampling technique with the Slovin formula of 335 people. Data collection was carried out using a questionnaire technique, the data collected was analyzed using multiple regression analysis. The results of this study indicate the value of R2 (coefficient of determination) or R Square of 0.298 or 29.8%. This value can be interpreted that changes in student achievement by changes in the value of independent variables learning motivation and learning creativity by 29.8% while 70.2% is determined by changes in other factors. The tcount for the learning motivation variable is 8.126 with sig. 0,000 is smaller than 0.05, this means there is an influence of learning motivation on student achievement and the tcount for learning creativity variable is 7,326 with sig. 0,000 less than 0.05, this means that there is an influence of learning creativity on student achievement. It can be concluded that there is an influence between learning motivation and learning creativity on student achievement in Islamic Religious Education Subjects in State Madrasah Aliyah in Pekanbaru City.